Measurement of dijet cross sections for events with a leading neutron in photoproduction at HERA - Breitweg, J; Chekanov, S; Derrick, M; Krakauer, D; Magill, S; Musgrave, B; Pellegrino, A; Repond, J; Stanek, R; Yoshida, R; Mattingly, M; Antonioli, P; et al. (2001)
Differential cross sections for dijet photoproduction in association with a leading neutron using the reaction e+ + p → e+ + n + jet + jet + Xr have been measured with the ZEUS detector at HERA using an integrated luminosity of 6.4 pb-1. The fraction of dijet events with a leading neutron in the final state was studied as a function of the jet kinematic variables. The cross sections were measured for jet transverse energies EjetT > 6 GeV, neutron energy En > 400 GeV, and neutron production angle θn < 0.8 mrad. The data are broadly consistent with factorization of the lepton and hadron vertices and with a simple one-pion-exchange model. © 2001 Elsevier Science B.V. All rights reserved.